Phototrophic Bacteria - Blankenship, Robert; Sattley, Matthew (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Microorganisms is pleased to publish this book, which reprints papers that appeared in a Special Issue on "Phototrophic Bacteria", with Guest Editors Robert Blankenship and Matthew Sattley. This Special Issue included research on all types of phototrophic bacteria, including both anoxygenic and oxygenic forms. Research on these bacterial organisms has greatly advanced our understanding of the basic principles that underlie the energy storage that takes place in all types of photosynthetic organisms, including both bacterial and eukaryotic forms. Topics of interest include: microbial physiology, microbial ecology, microbial genetics, evolutionary microbiology, systems microbiology, agricultural microbiology, microbial biotechnology, and environmental microbiology, as all are related to phototrophic bacteria.